Tujuh Fokus Pemimpin Pasar - Setiadi Umar (Center for Economic Studies Universitas Katolik Parahyangan, 2004)
Becoming a market leader is not an easy task, many things should be done and many have been done by market leader. However by becoming a market leader, doesn't mean that the tasks in hand have been completed. Actually it's far from completed, and there are many jealous rivals that try to wrest over the market leadership in many ways at any cost. Based on 3 disciplines values: product leader, operationally excellent firm, and customer intimate firm, that was written by Michael Treacy and Fred Wiersema, writer tries to highlight seven areas that should be brought into account in order to maintain market leadership: Market Sensing, Creativity, Range of Competencies, Speed, Operational Effectiveness, Loyalty Program, and Stakeholders Interest.